What are the individual and joint impacts of key meteorological factors on the risk of unintentional injuries? A case-crossover study of over 147, 800 cases from a sentinel-based surveillance system. (April 2023) - Lin, Xiao; Tian, Tian; Shi, Congxing; Wang, Pengyu; Chen, Shimin; Guo, Tong; Li, Zhiqiang; Liang, Boheng; Zhang, Wangjian; Qin, Pengzhe; Hao, Yuantao
Highlights: Meteorological factors were significantly associated with unintentional injury. The excess risk for precipitation and temperature was positive from lag0–1 day onward. Overall excess risk for relative humidity (RH) was negative from lag0-2 days onward. Workers, males, and patients injured by falls or with fractures were more vulnerable. High temperature and wind speed, with low precipitation and RH posed the highest risk. Abstract: Meteorological factors are a critical component of a sustainable society, especially in the context of climate change. Although studies have linked key meteorological factors to unintentional injuries, their joint effects on the occurrence of unintentional injuries remain unclear. We conducted a case-crossover study using a sentinel-based injury database in a mega-city in China and identified the vulnerable subgroups by demographic and injury characteristics. We observed significantly increased cumulative risk associated with each interquartile range increase in temperature (excess risk [ER] range=4.78–7.05%) and precipitation (ER range=1.00–2.09%) from lag0–1 day onwards. Conversely, there was a significantly decreased risk with relative humidity (RH) from lag0–2 days onwards (ER range=-2.83 to -2.10%). The link between meteorological factors and unintentional injuries was worthy of particular attention for the working-age groups, males, and those with fall-related injuries, road-related injuries, or fractures. Climate conditions with high wind speed (WS) and temperature combined with low precipitation and RH exhibited the greatest ER. The ER of high WS and RH, combined with low precipitation and temperature, was also significant. These key factors may jointly contribute to unintentional injury, which is important for evidence-based climate mitigation and injury prevention.